Factibilidad para la creación de una empresa productora y comercializadora de vasos con botellas de vidrio recicladas, en la ciudad de Loja provincia de Loja - Balcázar Reyes, Sandra Aurora (2023)
The present work of curricular integration is based on the investment projects that allow to evaluate, analyze the advantages and disadvantages at the time of the beginning and development of the activities of the company, the objective is to determine the feasibility for the creation of a production company and marketer of glasses with recycled glass bottles, the research has a quantitative approach, using the deductive method of an exploratory and descriptive type with a non-experimental design, for which it was necessary to use certain materials and methods, which allowed the collection and analysis of relevant data for its development. In the results of the market study, it was possible to determine an unsatisfied demand for year zero of 483,135 glass glasses; in the technical study where the installed capacity was taken into account, which determined that the company has the capacity to produce 157,680 glass glasses and whose used capacity will be 37,440 glass glasses. In the financial study, to start its activities, the company requires an investment of $24,722.23 US dollars, of which 59.55% will be financed with the contribution of the partners and 40.45% with a loan to Ban Ecuador; The financial evaluation determined: Net Present Value (VAN) 44.898,48 dollars, Internal Rate of Return (IRR) 68.52%, Capital Recovery Period (PRC) 2 years, 2 months and 16 days, Cost Benefit Ratio (RBC ) 0.37 US cents, and in the sensitivity analysis for the increase in costs it is 69.30%, and the decrease in income is 34.50%, once all the financial indicators and the sensitivity indicators are analyzed, may conclude that the project is feasible for implementation.